Konsep Etika Komunikasi Bermedia Sosial Bagi Generasi Milenial Perspektif Al-Qur’an - Amelia, Ulfi; Nasrulloh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This research aims to explain the analysis of the concept of social media communication ethics for the millennial generation from the perspective of the Qur'an. This study uses a qualitative approach with a descriptive method of literature analysis. This research applies primary sources and secondary sources. The results of the study show that there are 6 concepts of social media communication ethics from the perspective of the Qur'an, including Qaulan ma'rufan, kariman, maysuran, balighan, layyinan, and sadidan. Qaulan maysuran is one of the guidelines for communicating using language that is easy to understand and relieves feelings. The social media users who connect online vary, so it's important to consider the importance of communicative understanding. Communicators do not use language or write sentences that are difficult to understand. The goal is to unify perceptions between communicators and communicators, not just to improve communicative understanding. Therefore, it is very important to consider ethics when communicating, whether in person, in groups, with the masses, or through social media. However, before sharing an upload, social users should consider their role as communicators and communicators. The communicator must be responsible for all responses that may arise from the post and must be ready to receive criticism and feedback from the communicator.